Comparative corporate governance : legal perspectives - Magnier, Véronique (Edward Elgar Publishing, 2017)
Comparative Corporate Governance considers the impact of globalization on corporate governance issues and highlights how, despite the effect it has clearly had, predictions of legal convergence have not come true. By adopting a comparative legal approach, this book explores the tensions that exist between convergence attempts and the persistence of local models of governance in the US, Europe and Asia. Véronique Magnier assesses institutional, cultural and sociological factors as features of the disparities in governance. She does so by addressing the three main areas of tension in the legal aspects of corporate governance: theoretical pressure, which pits shareholder primacy against models advocating for greater participation of large corporations in general economic welfare; technical regulation, such as integrating corporate governance codes into national legal systems; and the need for context and reflection when transplanting governance approaches to different countries. Varying economic, societal and cultural environments make it vital to contextualize corporate governance in order to better understand how governance models operate in a globalized world. Lawyers, academics and advanced students of law looking to improve their understanding of corporate governance will find this a diverse and rewarding read.